Pengaruh Sengketa Laut China Selatan Terhadap Peningkatan Illegal Fishing di Perairan Sulawesi - Chantika Noer Aulia; Agussalim Burhanuddin (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
Beyond traditional armed conflicts, sovereignty threats may also arise through non-military means such as unilateral territorial encroachment. One of the pressing issues currently confronting Indonesia is the increasing occurrence of unauthorized fishing, which poses a serious risk to the country’s maritime security. This paper explores how the intensifying dispute in the South China Sea indirectly influences the surge in illegal fishing within Indonesian waters, particularly around Sulawesi. Escalating regional tensions have disrupted the governance and oversight mechanisms responsible for managing Indonesia’s marine resources, especially in its eastern maritime zones. This study employs a qualitative approach through an in-depth literature review. Descriptive analysis is used to identify recurring patterns and underlying factors driving the rise of unlawful fishing practices.